NON-COMPLIANCE TO ANTI-HYPERTENSIVE MEDICATION AND ITS ASSOCIATED FACTORS AMONG HYPERTENSIVES - Bilal, Arshia; Riaz, Mehwish; Shafiq, Noor- ulain; Ahmed, Mariam; Sheikh, Sadaf; Rasheed, Sobia (Journal of Ayub Medical College Abbottabad, 2015)
Background: Non-compliance to anti-hypertensive drugs can have negative impact on cardiovascular outcome. Various studies have been conducted on the issue but the factors are not yet explored properly, particularly in Pakistan. This study was conducted to determine the frequency and factors associated with non-compliance to anti-hypertensive medications in Karachi. Methods: This descriptive cross sectional study was conducted on 113 indoor hypertensive patients included by purposive sampling, aged 30 years and above diagnosed at least 6 months back in public sector tertiary care institutes of Karachi from March to October 2011. Data was collected through a questionnaire in Urdu. Demographic data, hypertension diagnosis, medical co-morbidity, current number of anti-hypertensive medicines, frequency of missing prescribed antihypertensive therapy and other factors affecting compliance pertaining to medicines, patient, physician and health care centre were included in the questionnaire. Results: This study revealed that 68.14% patients were non-compliant. Non-compliance was found to be associated with gender and socioeconomic status. Duration of hypertension, duration between follow up visits to physician, number of drugs, careless attitude, role of physician and limiting access to health care center are found to be important factors in non-compliance. Conclusions: Multiple factors including patients, medicine and health care system related, which can be prevented with simple measures, were found responsible for higher prevalence of non-compliance against anti-hypertensive medicines. Keywords: Non-compliance, antihypertensive drugs, risk factors for non-compliance, tertiary care hospital.